2017
DOI: 10.1002/ccd.27200
|View full text |Cite
|
Sign up to set email alerts
|

Second generation drug‐eluting stents versus bare‐metal stents for percutaneous coronary intervention of the proximal left anterior descending artery: An analysis of the BASKET‐PROVE I and II trials

Abstract: In patients with proximal LAD stenosis, treatment with second-generation DES was associated with reduced 2-year rates of adverse cardiac events and TVR compared to BMS, with reintervention rates similar to those earlier reported from bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Furthermore, the intravascular imaging included in our study includes IVUS and OCT. Meanwhile, our study included all types of DES, new-generation of DES may lead to better clinical outcomes [ 32 , 33 ]. However, the subgroup analysis of the first or second-generation and new-generation DES in this study did not get a positive result, which may be related to insufficient sample size and different trials have been associated with different definitions of clinical outcomes.…”
Section: Limitationmentioning
confidence: 99%
“…Furthermore, the intravascular imaging included in our study includes IVUS and OCT. Meanwhile, our study included all types of DES, new-generation of DES may lead to better clinical outcomes [ 32 , 33 ]. However, the subgroup analysis of the first or second-generation and new-generation DES in this study did not get a positive result, which may be related to insufficient sample size and different trials have been associated with different definitions of clinical outcomes.…”
Section: Limitationmentioning
confidence: 99%
“…[2][3][4] The development of DES was considered as another pronounced leap in the field of interventional cardiology and various clinical trials demonstrated the superiority of DES over BMS with significant decrease in the target lesion revascularisation (TLR) and ISR rates. [6][7][8][9][10][11] However, with the incidence of late stent thrombosis, the usage of earlier generation DES with durable polymers and thick strut reduced significantly. This led to another breakthrough in the development of newer generation DES with thinner struts that were coated with biodegradable polymers and newer antiproliferative agents.…”
Section: Introductionmentioning
confidence: 99%
“…Имплантация ГМС, представляющих собой металлический каркас, была сопряжена с повышенной тромбогенностью и вероятностью рестеноза ранее стентированного сегмента. Нанесение на стент лекарственного покрытия подавляет избыточную пролиферацию неоинтимы и снижает вероятность рестеноза по сравнению с таковыми при использовании непокрытых (голометаллических) стентов [2][3][4].…”
unclassified